Long-term Effects of Munisipal Solid Waste Leachate on Soil Geotechnical Properties - Chihi, Feten; Kopecskó, Katalin; Varga, Gabriella (Periodica polytechnica. Civil engineering. Bauingenieurwesen, 2025)
This study investigates the long-term effects of landfill leachate contamination on soil hydraulic conductivity and shear strength parameters over a 12-month period, addressing the current lack of comprehensive long-term experimental data in this field. Laboratory permeability tests and direct shear tests were performed on sandy clayey silt samples contaminated with leachate at concentrations ranging from 5% to 25%. Microstructural and mineralogical analyses were conducted using SEM and XRD to identify the mechanisms behind observed changes. The results identify a critical threshold at 15% contamination where soil behavior transitions from granular to cohesive characteristics, marked by significant changes in both hydraulic and mechanical properties. Hydraulic conductivity increases at low contamination levels but decreases significantly at higher levels, while friction angle shows an immediate reduction from 36.5° to 31-31.5° and cohesion exhibits a three-phase evolution pattern, reaching peak increases of 151.5% at 15% contamination. The hydraulic conductivity changes are controlled by contamination level rather than exposure time, maintaining stable values throughout the testing period, whereas shear strength parameters demonstrate more complex temporal evolution patterns. These findings provide essential parameters for landfill design and stability assessment, demonstrating how leachate concentration affects long-term soil behavior through mineral formation and structural modification.